Small needle decompression is equally effective like chest drain in a case of massive pneumothorax: a case report - Bhowmik, Dr.Amit (IJRDO -JOURNAL OF HEALTH SCIENCES AND NURSING, 2016)
A 64 yrs,male patient presented with sudden onset of respiratory distress for which he wasadmitted in some other hospital.The symptoms were mild there on presentation which increasedgradually and he was shifted to Glocal hospital, Krishnanagar for further management. Thepatient had a recent history of hospitalization in the same hospital for LRTI, urosepsis andarrhythmia. He is also a case of Ca-urinary bladder. He was recovered from the respiratoryinfection with a residual cough during the last visit.